Do surrounding figures' emotions affect judgment of the target figure's emotion? Comparing the eye-movement patterns of European Canadians, Asian Canadians, Asian international students, and Japanese - Masuda, Taka; Wang, Huaitang; Ishii, Keiko; Ito, Kenichi (Frontiers in Integrative Neuroscience, 2012)
Although the effect of context on cognition is observable across cultures, preliminary findings suggest that when asked to judge the emotion of a target model's facial expression, East Asians are more likely than their North American counterparts to be influenced by the facial expressions of surrounding others (Masuda et al., 2008b). Cultural psychologists discuss this cultural variation in affective emotional context under the rubric of holistic vs. analytic thought, independent vs. interdependent self-construals, and socially disengaged vs. socially engaged emotion (e.g., Mesquita and Markus, 2004). We demonstrate that this effect is generalizable even when (1) photos of real facial emotions are used, (2) the saliency of the target model's emotion is attenuated, and (3) a specific amount of observation time is allocated. We further demonstrate that the experience plays an important role in producing cultural variations in the affective context effect on cognition.